The Use of Oil Palm Frond for Beef Cattle Feed of Cattle Farming Community Enterprise in Sichon District, Nakhon Si Thammarat Province - Pimpa, Opart; Lertritchai, Chaiyapong; Sripuck, Wuttichai; Khamseekhiew, Bodee; Pimpa, Benchamaporn (Area Based Development Research Journal, 2020)
Promoting the use of oil palm frond for beef cattle raising of 3 community enterprise groups in Sichon District, Nakhon Si Thammarat Province was conducted in these groups: 1) Thung Sai beef cattle community enterprise group 2) Thung Prang beef cattle community saving group and 3) Sao Phao beef cattle community group. The total number of members of all 3 groups were 90 people. The objectives were to solve problems of lack of cattle feed and to determine the guideline for raising cows in combination with oil palm plantations. There were 6 steps of the change process: 1) Organizing a workshop on using oil palm frond for cattle feed, 2) Farmer group development by establishing a learning center for raising beef cattle, 3) Formulating a 2-year group action plan, 4) Procurement and support of animal feed mixing equipment, 5) Helping farmers facing beef cattle feed problems, 6) Monitoring and following up with the members. From the 3-year implementation (2016-2018), the use of oil palm frond for feeding increased the oil palm frond value of 6,000 baht per rai per year. The saving from using oil palm frond was 600 baht per day on each farm. All three sub-districts successfully established a learning center on the utilization of oil palm frond in beef cattle raising. This operation has led the farmers to have higher income, to reduce animal feeding costs by 35% and to gain higher profits by 26% from the sale of cattle during the fattening period of 6 months, in comparison with situation before the operation. In conclusion, the farmers received more tools and equipment from government agencies and achieved success in various projects, namely, winning the first prize in the Cattle-Buffal Bank Project for farmers under the Royal Initiative Outstanding level 1, Office of Livestock Development, Region 8, for two consecutive years.